Nematode Behaviour - Gaugler, Randy (CABI, 2014)
Nematodes inhabit virtually every environment and are among the most ubiquitous organisms on earth. Four of every five metazoans is a nematode, and a mere 100 g of soil typically will house 3000 individuals. With an estimated 1 million species, only insects rival nematodes in biodiversity. Nematology, the youngest of the zoological disciplines, is splintered along taxonomic lines into plant, insect, animal and human-parasitic, and free-living nematode factions. Historically these disparate discipline camps have communicated poorly, when at all. The bewildering differences in terminology (e.g. juvenile vs. larva) among the subdisciplines are products of this separation. In recent years, however, these barriers have become more fluid due to common interest in the extraordinary fundamental advances being made by molecular biologists with the free-living nematode, Caenorhabditis elegans.